To Raise Awareness of Students of Higher Education in the Field of Uzbek Folk Music from the Culture of the Ancient East to the Present Day - Ma’rufjon Ashurov Abdumutalibovich (Research Parks Publishing LLC, 2021)
In the middle of the 3rd century BC, the Parthian states were formed in the western regions of Central Asia, and the Greco-Bak Bakreia states in the east. In the first century AD, a powerful Kushan kingdom was formed in the southern part of Central Asia. Under the rule of the local Kushan dynasty, a number of states were united, as a result of which cities flourished, culture flourished, and conditions were created for the creation of new musical instruments.